Molluscoid pseudovesicles: An unusual presentation of sweet's syndrome - Aditya Kumar Bubna; Sudha Rangarajan (Wolters Kluwer Medknow Publications, 2015)
Sweet's syndrome is a well-known entity in the field of dermatology. It has presented itself in myriad forms, well-recorded in literature. Our patient presented with a sudden eruption of nontender molluscoid pseudovesicles distributed over the neck and forearms alone. A complete diagnostic work up for the same did not give any clue regarding an underlying systemic ailment, responsible for the dermatosis. This case is being presented because of this extremely rare morphology of Gomm-Button disease.